REPORT ON THE FIRST WORKSHOP OF EAST-AFRICA NETWORK OF EXCELLENCE FOR UNIVERSITIES OF APPLIED SCIENCES HELD ON 5th -12th October 2018 AT HOCHSCHULE NEU-ULM UNIVERSITY OF APPLIED SCIENCES (HNU) AND TECHNISCHE HOCHSCHULE INGOLSTADT (THI) - Mulwa, David; Abungu, Nicodemus (My University, 2018)
The workshop was held on 5th to 12th October 2018 and was hosted by HNU and THI universities in Bayern (Bavaria) State, Germany. The workshop was sponsored by German Academic Exchange Service (DAAD) and was attended by 17 participants from Seven Kenyan Universities. Dr. David Mulwa from the School of Education and Professor Nicodemus Abungu from the School of Engineering in Machakos University attended the workshop.